Management of Absent Capsular Support with a new Intraocular Lens Design - M Ghoneim, Ehab (Journal of Ophthalmic Science, 2015)
Purpose: To describe a new intraocular lens that can be implanted in case of rupture of the posterior capsule and lack of capsular support. Methods: This experimental study was carried out on ten Flanders rabbits. The right eye of each rabbit underwent intra capsular lens extraction and two peripheral iridectomies, and the new lens was implanted with an optic rest in the posterior chamber. Additionally, the haptics rest in the angle of the anterior chamber through peripheral iridectomies. Main outcome measures were lens stability inside the eye and complications regarding this technique. Results: Intraocular lenses remained in a stable position with only a mild inflammatory reaction; four eyes developed hyphema that disappeared 10 days after surgery. Conclusion: The new lens design has good intraocular stability when posterior capsular support is absent and only produced minimal inflammation inside the eye.
Keywords: Aphakia correction; Zonulysis; lens subluxation.